The Effect of Variations in the Concentration of Added Butyrum (milk fat) on the Making of Paper Soap and Organoleptic Properties: Sensory Tests and Product Stability - Rahmawati, Sri Tria; Haryanto, Haryanto (Journal of Engineering Science and Technology Management (JES-TM), 2026)
This study aims to determine the effect of variations in the concentration of butyrum (milk fat) addition on the quality of paper soap, including organoleptic properties, pH, free alkali, and solubility. Paper soap is made by the hot process method using the main ingredients of VCO, NaOH, distilled water, HPMC, camperlan, 96% ethanol, citric acid, and butyrum with 25 formulation variations. Organoleptic tests are carried out based on observations of color, aroma, texture, and foam volume. The pH test aims to ensure the acidity level of the soap is safe for the skin, the free alkali test is carried out by the titration method, and the solubility test measures the dissolving time of the soap in water. The results show that variations in butyrum concentration affect the physical properties of paper soap, especially the texture and foam produced. The pH value of the soap is in the range of 8–9 with an average of 8.5, thus meeting SNI standards. The free alkali test shows that all formulas are below the maximum limit of 0.1%, so it is safe to use. The dissolution time of the paper soap is in the range of 1–3 minutes, indicating good solubility. Overall, the addition of butyrum has a positive effect on the organoleptic quality and stability of paper soap.